Pseudobacteremia due to contaminated alcohol swabs. - Berger, S A (1983)
Fifteen isolates of Bacillus species were recovered during a 19-day period after the introduction of an automated radiometric blood culture system. The outbreak was traced to alcohol-resistant spores present in the cotton used to disinfect blood culture bottles. The role of Bacillus species as a pathogen and a laboratory contaminant is discussed.